Effects of simvastatin, ezetimibe and simvastatin/ezetimibe on mitochondrial function and leukocyte/endothelial cell interactions in patients with hypercholesterolemia. (April 2016) - Hernandez-Mijares, Antonio; Bañuls, Celia; Rovira-Llopis, Susana; Diaz-Morales, Noelia; Escribano-Lopez, Irene; de Pablo, Carmen; Alvarez, Angeles; Veses, Silvia; Rocha, Milagros; Victor, Victor M.
Abstract: Background: Cholesterol-lowering therapy has been related with several beneficial effects; however, its influence on oxidative stress and endothelial function is not fully elucidated. Aims: To investigate the effect of simvastatin and ezetimibe on mitochondrial function and leukocyte–endothelium interactions in polymorphonuclear cells of hyperlipidemic patients. Methods: Thirty-nine hyperlipidemic patients were randomly assigned to one of two groups: one received simvastatin (40 mg/day) and the other received ezetimibe (10 mg/day) for 4 weeks, after which both groups were administered combined therapy for an additional 4-week period. Lipid profile, mitochondrial parameters (oxygen consumption, reactive oxygen species (ROS) and membrane potential), glutathione levels, superoxide dismutase activity, catalase activity and leukocyte/endothelial cell interactions and adhesion molecules -VCAM-1, ICAM-1, E-selectin, were evaluated. Results: An improvement in lipid profile was observed after administration of simvastatin or ezetimibe alone (LDLc: −40.2 vs −19.6%, respectively), though this effect was stronger with the former (p < 0.001), and a further reduction was registered when the two were combined (LDLc: −50.7% vs −56.8%, respectively). In addition to this, simvastatin, ezetimibe and simvastatin + ezetimibe significantly increased oxygen consumption, membrane potential and glutathione content, and decreased levels of ROS, thereby improving mitochondrial function. Furthermore, simvastatin + ezetimibe increased catalase activity. In addition, simvastatin and simvastatin/ezetimibe improved leukocyte/endothelium interactions by decreasing leukocyte rolling and adhesion and increasing leukocyte rolling velocity. Finally, simvastatin, ezetimibe and simvastatin + ezetimibe reduced levels of the adhesion molecule ICAM-1, and ezetimibe + simvastatin significantly decreased levels of E-selectin. Conclusion: Co-administration of simvastatin and ezetimibe has an additive cholesterol-lowering effect and beneficial consequences for mitochondrial function and leukocyte/endothelium interactions in leukocytes of hypercholesterolemic patients. Graphical abstract: Highlights: Hyperlipidemic patients were treated with simvastatin/ezetimibe (40/10 mg) for 8 weeks. We measured mitochondrial function, superoxide dismutase and catalase activity and leukocyte/endothelium interactions. Statin and ezetimibe has an additive cholesterol lowering effect. Combined therapy has beneficial effects on mitochondrial and endothelial function. Statin plus ezetimibe may protect from cardiovascular diseases in hyperlipidemia.